Pediatric cochlear implant explantation and reimplantation over a 32-year period. (March 2023) - Hou, Vincent; Tellez, Paula; Fandiño, Marcela; Ospina, Juan; Chia, Ruth; Bergstrom, Raegan; Riding, Keith; Kozak, Jessica; Kozak, Emelie; Pauwels, Julie; Kozak, Frederick
Abstract: Objectives: Cochlear implantation is indicated for pediatric patients with bilateral severe to profound sensorineural hearing loss. The literature reports large variability in cochlear implant (CI) device survival and rates of explantation and reimplantation. This retrospective chart review summarizes CI survival and rates of explantation and reimplantation in pediatric CI recipients at a Canadian tertiary pediatric hospital over 32 years. Methods: A retrospective chart review of all pediatric patients who received a Cochlear Corporation® CI between April 1988 and June 2020 was undertaken. Rates of explantation/reimplantation were collected and categorized based on device type and reason for failure (medical, device, and inconclusive failure). Device survival analysis based on implant model was also completed utilizing Kaplan-Meier curves. Results: 512 CIs were implanted over the 32-year period by four surgeons (77.1%, 18.16%, 4.49%, and 0.20%, respectively). Patient age ranged from seven months to 20.4 years. The overall explantation and reimplantation rate was 3.32% (17/512 implants), with seven as a result of device failure (1.37%), nine events of medical failure (1.76%), and one inconclusive failure (0.20%). Cumulative CI survival rates at 5, 10, 15, and 20 years were 98.15%, 96.33%, 95.53%, and 94.39%. Conclusion: The overall institutional CI failure, explantation, and reimplantation rates are lower than the average reported rates in the literature. Highlights: Pediatric cochlear implant recipients at BC Children's Hospital had favorable outcomes. Rates of device and medical failures were lower than those reported in the literature. Older cochlear implant models and the CI512 had higher rates of failure.